(untitled) (Eurasian Journal of Philology Science and Education, 2018)
Bayshyganuly Kodek is one of the literary figures in the history of Kazakh literature, whose creative life has recently subjected to careful study. The main essence of the poet is a vague time spent by people in the early twentieth century. The historical truth of events in 1916, after a sharp order of white Tsar about the transmigration of people with an amply situated place organising bustle accepts a wide artistic scope in the Kazakh literature. The truth of those days is detailed in prose and poetry. This topic has formed as one of the urgent topics in the development of Kazakh literature. Zhusypbek Aimauytov, Saken Seifullin, Mukhtar Auezov, Sabit Mukanov, Gabit Musrepov, Askar Suleimenov, etc. wrote their prosaic works, where the main topic was the human destinies of a troubled time. The poetry of the poem «Bekbolat» by Omar Chapin is studied in school textbooks. One of the countless victims of dodgy politics of that era is a gifted poetic figure Kodek Bayshyganuly.